Analysis of complete genome sequence and major surface antigens of Neorickettsia helminthoeca, causative agent of salmon poisoning disease. Issue 4 (6th June 2017) - Lin, Mingqun; Bachman, Katherine; Cheng, Zhihui; Daugherty, Sean C.; Nagaraj, Sushma; Sengamalay, Naomi; Ott, Sandra; Godinez, Al; Tallon, Luke J.; Sadzewicz, Lisa; Fraser, Claire; Dunning Hotopp, Julie C.; et al.
Summary: Neorickettsia helminthoeca, a type species of the genus Neorickettsia, is an endosymbiont of digenetic trematodes of veterinary importance. Upon ingestion of salmonid fish parasitized with infected trematodes, canids develop salmon poisoning disease (SPD), an acute febrile illness that is particularly severe and often fatal in dogs without adequate treatment. We determined and analysed the complete genome sequence of N. helminthoeca : a single small circular chromosome of 884 232 bp encoding 774 potential proteins. N. helminthoeca is unable to synthesize lipopolysaccharides and most amino acids, but is capable of synthesizing vitamins, cofactors, nucleotides and bacterioferritin. N. helminthoeca is, however, distinct from majority of the family Anaplasmataceae to which it belongs, as it encodes nearly all enzymes required for peptidoglycan biosynthesis, suggesting its structural hardiness and inflammatory potential. Using sera from dogs that were experimentally infected by feeding with parasitized fish or naturally infected in southern California, Western blot analysis revealed that among five predicted N. helminthoeca outer membrane proteins, P51 and strain‐variable surface antigen were uniformly recognized. Our finding will help understanding pathogenesis, prevalence of N. helminthoeca infection among trematodes, canids and potentially other animals in nature to develop effective SPD diagnostic and preventive measures. Recent progresses in large‐scale genome sequencing have been uncovering broad distribution of Neorickettsia spp., the comparative genomics will facilitate understanding of biology and the natural history of these elusive environmental bacteria. Abstract : Neorickettsia helminthoeca, an obligatory intracellular bacterium of digenetic trematodes, is the causative agent of salmon poisoning disease, an acute and often fatal illness in dogs. We provide in this report the complete genome sequence of N. helminthoeca Oregon strain, the comparative analysis with other members in the family Anaplasmataceae, and the antigenic analysis of N. helminthoeca outer membrane proteins. These findings will facilitate the understanding of the biology and pathogenesis of this bacterium, and provide tools for developing rapid diagnostic methods and new prevention strategies against salmon poisoning disease.